Analisis Pengelolaan Keuangan Sekolah Di SMA Muhammadiyah Se Surakarta - HANDAYANI, DWI; , Tri Nur Wahyudi, S.Pd, MM (2017)
This study aims to find out how the planning and budget realization in financial management, and how big the budget realization of budget planning in SMA Muhammadiyah se Surakarta. This type of research is to use mixed methods with mixed design concurrent design. The population in this study is SMA Muhammadiyah se Surakarta and the sample taken 2 (two) schools namely SMA Muhammadiyah 3 Surakarta and SMA Muhammadiyah 6 Surakarta. Data collection technique is done by observation, interview, and document review. Qualitative data analysis technique used is triangulation, while quantitative data analysis techniques using descriptive statistical analysis. Based on the results of data analysis, planning and budget realization in school financial management in SMA Muhammadiyah se Surakarta has been implemented effectively and efficiently in accordance with the applicable regulations. For budget realization of budget planning in SMA Muhammadiyah 3 Surakarta reaches 90%, while in SMA Muhammadiyah 6 Surakarta reach 80%. This is due to the lack of funding constraints faced by schools.